Pendidikan Karakter melalui Revolusi Mental di Era Disruptif - Sholekhah, Fitriatus (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2019)
The Indonesian nation is a developing country that is rich in its natural resources, but this country is still developing after 70 years of independence, the ideal of the Indonesian state is to make a nation that is civilized in accordance with norms and religion. What is wrong with this nation, so that the Indonesian people remain a developing country? Character education is the most important asset in a country, because the progress of a country depends on the character of the nation's children. In tackling character education that has deteriorated further, the mental revolution is the solution, a movement that was initiated by Indonesia's first president, Ir. Soekarno and was developed by President Jokowi as the 7th President of the Republic of Indonesia in his campaign in 2014. The current state of Indonesia is a character crisis for the nation, fighting between students, sexual violence, taking drugs, drugs and others. In welcoming the disruptive era where information technology is increasingly advanced and very easy. Where the nation's children still cannot distinguish between the good and the bad, the obligation of an educator who must guide and foster in the process of character development in the disruptive era.